Empowering Orphaned Youth: Digital Business as a Catalyst for Entrepreneurial Readiness at PAKYM Muhammadiyah Orphanage - Rudi Kurniawan; Sisca Dian Rahmawati; Risanda Alirastra Budiantoro; Erin Kristina; Nadiya Fikriyatuz Zakiyah (JOCESS : The Journal of Community Empowerment and Sustainability Services, 2025)
This community service program aims to provide comprehensive education on increasing income through digital entrepreneurship (e-commerce) and training and mentoring in creating accounts and stalls on e-commerce, determining products and prices, promotions, packaging, and distributing products through expedition services. The method in this program is IbM (Science and Technology for Society), which is carried out through education and direction in two-way communication (duplex), followed by e-commerce skills training and mentoring for digital business implementation simulations. The results of the entrepreneurial skills improvement program through e-commerce as a business startup media are carried out in stages: (1) IbM method, namely training in registration and management of e-commerce profiles; (2) Managing e-commerce accounts periodically until sales occur; (3) Selling and making reports on online businesses that have been run. Mentoring activities to create a business plan can encourage PAKYM Children at the Muhammadiyah Orphanage to independently and innovatively develop ideas, goals, and strategies and implement digital businesses that will run effectively.